2019
DOI: 10.1186/s12913-019-4199-6
|View full text |Cite
|
Sign up to set email alerts
|

Decision making tools for managing waiting times and treatment rates in elective surgery

Abstract: Background Waiting times for elective treatments, including elective surgery, are a source of public concern and therefore are on policy makers’ agenda. The long waiting times have often been tackled through the allocation of additional resources, in an attempt to reduce them, but results are not straightforward. At the same time, researchers have reported wide geographical variations in the provision of elective care not driven by patient needs or preferences but by other factors. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 35 publications
0
19
0
3
Order By: Relevance
“…This paper adapted the waiting times-admission rate matrix already used in other services [44][45] to the ED context, using the illustrative example of Tuscan EDs. The matrix can work as a logical diagnostic tool to help managers analyse the situation of their EDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper adapted the waiting times-admission rate matrix already used in other services [44][45] to the ED context, using the illustrative example of Tuscan EDs. The matrix can work as a logical diagnostic tool to help managers analyse the situation of their EDs.…”
Section: Discussionmentioning
confidence: 99%
“…To provide a diagnostic logical framework to detect the specific situation and the factors influencing ED waiting times, we propose a descriptive study based on a matrix that compares ED waiting times with the ED admission rate. This framework has been designed and applied to other services [44,45].…”
Section: The Diagnostic Framework To Cope With Ed Waiting Timesmentioning
confidence: 99%
“…Given that Tuscany is the Italian region with the highest number of robotic surgical systems per capita (1 unit every 287 000 inhabitants against a national average of 1 unit every 600 000 inhabitants), the ongoing debate around the cost of robotic surgery and the persisting unwarranted variation for surgical services, the regional administration has decided to put in place a routine collection of patient reported measures for patients who suffer from prostate, lung, or colorectal cancer and receive a robotic procedure.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Long delays can enable symptoms to deteriorate, and frustrate patients, surgeons and supporting staff. [5,6] The effi-ciency of the scheduled care system is immensely important for hospital stakeholders as surgery is often the greatest cost and source of revenue for hospitals, at times accounting for up to 60%-70% of hospital admissions. [7] Extended waiting times for elective surgery can be caused by a mismatch between waiting list demand and capacity, result-ing from inefficient capacity planning, [8] or challenges with the chronological management of patient bookings (process issues).…”
Section: Introductionmentioning
confidence: 99%
“…[11] However, reducing demand even when taking into consideration clinical and non-clinical parameters, may raise ethical dilemmas [11] and various studies concluded that demand may not necessarily be the cause for long waiting times. [5] Interestingly, other studies have suggested that the lack of capacity is not the major issue and funding extra sessions may be a suboptimal approach from a financial perspective, [8] but rather the root cause of patients waiting longer than clinically recommended timeframes is a combination of demand and capacity variation in conjunction with ineffective capacity planning. [8] Hence, there is a need for a targeted demand and capacity monitor to enable risk escalations and more effective theatre allocations.…”
Section: Introductionmentioning
confidence: 99%